2017
DOI: 10.4049/jimmunol.1601932
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C3b-Binding Small-Molecule Complement Inhibitors Using Cheminformatics

Abstract: The complement system is an elegantly regulated biochemical cascade formed by the collective molecular recognition properties and proteolytic activities of over two dozen membrane-bound or serum proteins. Complement plays diverse roles in human physiology which include acting as a sentry against invading microorganisms, priming of the adaptive immune response, and removal of immune complexes. However, dysregulation of complement can serve as a trigger for a wide range of human diseases which include autoimmune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The membrane bound C5a receptor also showed higher transcript abundance in livers of wild frogs compared with laboratory frogs. Although complement factors can bind alkaloids (Garcia et al, 2017), abundance can also be influenced by pathogens and other environmental factors (Gasque, 2004). Thus, further experiments with more controlled groups are necessary to determine whether these immunity factors are important for chemical defenses.…”
Section: Other Proteins Classes Of Interestmentioning
confidence: 99%
“…The membrane bound C5a receptor also showed higher transcript abundance in livers of wild frogs compared with laboratory frogs. Although complement factors can bind alkaloids (Garcia et al, 2017), abundance can also be influenced by pathogens and other environmental factors (Gasque, 2004). Thus, further experiments with more controlled groups are necessary to determine whether these immunity factors are important for chemical defenses.…”
Section: Other Proteins Classes Of Interestmentioning
confidence: 99%
“…To demonstrate the quantitative accuracy of the dual-species approach in binding studies we applied this model to a previously reported dataset involving the competitive binding of unlabeled and dye-labeled TRX-4W9A fusion protein to complement protein C3b immobilized on a sensor chip [10]. The binding dissociation constants (K D ) of the two protein species were previously determined in control experiments using serial dilution and a 1:1 binding model [10]. For the native protein, a kinetic evaluation yielded K D = 770 nM, while an equilibrium evaluation yielded K D = 590 nM [10].…”
Section: Resultsmentioning
confidence: 99%
“…On a Biacore T200, 700 RU of C3b-biotin was captured on a CMD-200 sensor chip (XanTec Bioanalytics) which had previously been amine coupled with NeutrAvidin Protein (Thermo Scientific). For the binding studies, the thioredoxin-compstatin fusion protein (TRX-4W9A) was produced and purified as described earlier [10]. For labeling of the protein, TRX-4W9A was dialyzed into phosphate buffered saline (pH 7.4) for 2 h at room temperature, and then incubated for 1 h in the dark with 5 molar excess of dye reagent Episentec B23 NHS ester (Episentum) followed by dialysis into HBS at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…For both search A and search B, pharmacophore models were generated on the basis of the resolved crystal structure of compstatin bound to human C3c (PDB code 2QKI( 22 )) as well as docked structures we produced from C3c in complex to cmp-5 (ZINC61197239), a compound recently shown to significantly inhibit the cleavage of C5, 51 a downstream process of the complement system. The pharmacophore models based on the binding of compstatin to C3c were developed using subsets of four features, each of which target an amino acid within one of four amino acid sectors of human C3c (sector I: 344–349, sector II: 388–393, sector III: 454–462, and sector IV: 488–492).…”
Section: Methodsmentioning
confidence: 99%